Acute physical stress induces the alteration of the serotonin 1A receptor density in the hippocampus. Issue 8 (10th May 2014) - Choi, Jae Yong; Shin, Sora; Lee, Minkyung; Jeon, Tae Joo; Seo, Youngbeom; Kim, Chul Hoon; Kim, Dong Goo; Yi, Chi Hoon; Lee, Kyochul; Choi, Tae Hyun; Kang, Jee Hae; Ryu, Young Hoon
ABSTRACT Stress affects the serotonergic system, which is associated with depression. Previous research has showed that chronic stress causes the deactivation of the limbic system. However, the influence of the acute physical stress on the serotonergic system in vivo was primarily unclear. The purpose of this research is to elucidate the effects of the acute physical stress in vivo using PET. For quantification of the 5‐HT1A receptors in the brain, we measured [18F]Mefway uptake in the two experiment groups (control and despair rats). The despair group was subjected to the external stressful situation (i.e., forced swimming) and total duration time of immobility, refers to the despair severity, and was analyzed. In the intercomparison experiment, the resulting PET images of [18F]Mefway in the despair rat displayed a significant reduction of radioactivity in the hippocampus (HP) compared with the control. The nondisplaceable binding potential (BPND) refers to the ratio of the concentration of radioligand in the receptor‐rich region (i.e., HP) to the concentration of that in the receptor‐free region (i.e., cerebellum). The hippocampal uptake and the BPND in the despair group were respectively about 25 and 18% lower than those of the control group. The ratio of specific binding to nonspecific binding in the despair group was 18% lower than that of the control. In the intracomparison experiments, the BPND and immobility in the despair group showed a strong negative correlation. Taken together, the data illustrates that an acute physical stress induces the change in the serotonergic system that correlates with the behavioral despair. Synapse 68:363–368, 2014. © 2014 Wiley Periodicals, Inc.